Numerical receipes in C : the art of scientific computing - Press, William H.; Teukolsky, Saul A.; Vetterling, William T.; Flannery, Brian P. (New Delhi : Cambridge University Press, 1992)
Computer science
2005-03-24
Keywords: Numerical receipe - C; Random numbers; Sorting; Eigensystems